2012
DOI: 10.1016/j.devcel.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 in the Dermal Papilla Niche Controls Hair Growth by Fine-Tuning BMP Signaling in Differentiating Hair Shaft Progenitors

Abstract: SUMMARY How dermal papilla (DP) niche cells regulate hair follicle progenitors to control hair growth remains unclear. Using Tbx18Cre to target embryonic DP precursors, we ablate the transcription factor Sox2 early and efficiently, resulting in diminished hair shaft outgrowth. We find that DP niche expression of Sox2 controls the migration rate of differentiating hair shaft progenitors. Transcriptional profiling of Sox2 null DPs reveals increased Bmp6 and decreased Bmp inhibitor Sostdc1, a direct Sox2 transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
117
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 55 publications
11
117
0
Order By: Relevance
“…Unexpectedly, conditional ablation of Sox2 in E14.5 DC allowed DPs and HFs to form. The resulting phenotype was modest and restricted to these three hair types (Clavel et al, 2012;Lesko et al, 2013). This suggests that expression of Sox2 is dispensable for dermal papilla specification, even if it could be important for some aspects of its function.…”
Section: Introductionmentioning
confidence: 87%
“…Unexpectedly, conditional ablation of Sox2 in E14.5 DC allowed DPs and HFs to form. The resulting phenotype was modest and restricted to these three hair types (Clavel et al, 2012;Lesko et al, 2013). This suggests that expression of Sox2 is dispensable for dermal papilla specification, even if it could be important for some aspects of its function.…”
Section: Introductionmentioning
confidence: 87%
“…Sox2 has important roles in the development of several endodermal tissues, such as the trachea (Xie et al, 2014) stomach and gut (Que et al, 2007), as well as in ectodermal tissues including the anterior pituitary (Jayakody et al, 2012), lens epithelium (Taranova et al, 2006), tongue epithelium and hair follicles (Clavel et al, 2012). Sox2 was recently identified as a marker for DESCs.…”
Section: Introductionmentioning
confidence: 99%
“…This structure acts as a signaling center to control stem cell fate (Clavel et al, 2012;Lane et al, 2014;Spradling et al, 2001). The precise and timely regulation of stem cell renewal and differentiation is essential for tissue formation, growth and homeostasis over the course of a lifetime (Moore et al, 2006), but the molecular mechanisms underpinning this regulation are variable and dependent on tissuespecific signaling and transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, conditional ablation of Sox2 in the DC at E14.5 has allowed DP and hair follicles to form. The resulting phenotype was modest and restricted to these three hair types (Clavel et al, 2012;Lesko et al, 2013). This suggests that expression of Sox2 is dispensable for DP specification even if it could be important for some aspects of its function.…”
Section: Introductionmentioning
confidence: 88%
“…An earlier study has also demonstrated that Sox2 ablation in the DC does not affect hair follicle formation. The study also suggested that Sox2 negatively regulates BMP signalling within the hair follicle, and its absence results in an inability for matrix progenitor cells to migrate to the hair shaft as they differentiate (Clavel et al, 2012).…”
Section: Sox2 and Sox18 In Dermal Papilla Specificationmentioning
confidence: 99%